PENGARUH KEPEMIMPINAN, MOTIVASI KERJA, LINGKUNGAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA GURU SEKOLAH DASAR KOTA CILEGON - Hardjono, Sonny; Affandi, Naufal; Umalihayati (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to explore more deeply how leadership, work motivation, work environment, and work discipline play a role in determining the performance of Elementary School teachers in Cilegon City. The approach applied in this study is quantitative correlational, where the research focuses on analyzing the relationship between these variables through surveys and questionnaire distribution. As the main data source, this study collected information from 300 Elementary School teachers in Cilegon City, which were then analyzed using descriptive statistical methods and multiple regression analysis. The findings of this study indicate that leadership and work discipline factors significantly have a positive impact on teacher performance. Meanwhile, work motivation and work environment factors do not show a significant influence on teacher performance in the context of this study.